FINDING THE YIELD ON A BOND. - Stelson, Hugh E. (The Accounting Review, 1951)
The purpose of this article is to apply modifications of Newton's method for approximating the root of an equation to the solution of bond problems which require very accurate determination of the interest rate. Repeated applications of Newton's formula will give any desired degree of accuracy. However, it is not practical to apply Newton's formula more than once since the value obtained by the first application will usually give a value of the interest rate for which the corresponding function can not be found in the table. It is desirable to find a formula which will give in a single application greater accuracy than Newton's formula and which has the advantage of using tabular values obtained from the original estimation of the interest rate. has been developed in several papers in mathematical journals but its value in solving bond problems has not received sufficient attention. The use of Newton's method is explained in an article by N. Lecher.